LINGUISTIC FEATURES OF ENGLISH STUDY PROGRAMS STUDENTS’ TEXT MESSAGES TO THEIR LECTURERS - Ifan Iskandar (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2020)
ABSTRACT This study aims to examine the linguistic features of English and Indonesian languages in students’ text messages sent to their lecturers. Content analysis is employed and the data are the linguistic features identified in 1,521 students’ text messages delivered to the lecturers. The findings confirm the results of the former studies in that the typographic features of emoticons, letter deletion, rebus writing, and phonetic spelling and morphological features of initialism, abbreviation, reduplication, truncation, and casual style of spoken dictions are employed—the features linguistically creating a special register called textese recognized by non-standard form or textisms. The mechanics of languages are featured by the lack of compliance with the conventional usage of full stops, commas, and capitals; even less than ten percent of spaces considered inevitably used are not conventionally emploed. Dominant uses of one-claused sentences feature the syntax of the languages. Keywords: linguistic features, text messaging, typography, morphology, and syntax.